2020
DOI: 10.1186/s12876-020-01316-w
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous stent placement for malignant hilar biliary obstruction: side-by-side versus stent-in-stent technique

Abstract: Background: Currently, side-by-side (SBS) and stent-in-stent (SIS) are the two main techniques for stent deployment to treat hilar biliary obstructions. Previous studies comparing these two techniques are very limited, and thus, no consensus has been reached on which technique is better. The purpose of this study is to compare the clinical efficacy and safety of SBS and SIS deployment via a percutaneous approach for malignant hilar biliary obstruction. Methods: From July 2012 to April 2019, 65 patients with ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…However, the left lobe, right anterior, or right posterior biliary tree should be selected based on pre-interventional CT or MRI imaging to ensure the best drainage. Atrophied liver secondary to longstanding biliary obstruction or portal vein thrombosis should be avoided[ 22 ].…”
Section: Endoscopic Drainagementioning
confidence: 99%
See 1 more Smart Citation
“…However, the left lobe, right anterior, or right posterior biliary tree should be selected based on pre-interventional CT or MRI imaging to ensure the best drainage. Atrophied liver secondary to longstanding biliary obstruction or portal vein thrombosis should be avoided[ 22 ].…”
Section: Endoscopic Drainagementioning
confidence: 99%
“…Regarding their efficacy, one prospective ( n = 69) and one retrospective ( n = 64) study showed that SIS and SBS deployment seem to be similar in terms of clinical success, stent patency and adverse events[ 22 , 23 ] . In addition, a meta-analysis of four studies which included 158 patients in total revealed no significant differences with respect to the rates of successful placement ( P = 0.799), successful drainage ( P = 0.617), early complications ( P = 0.738), late complications ( P = 0.744) and stent occlusions ( P = 0.606)[ 24 ].…”
Section: Endoscopic Drainagementioning
confidence: 99%
“…SBS technique involves parallel stenting using two stents [ 10 ], and SIS technique involves placing a second SEMS contralaterally through the first stent mesh [ 10 ]. Successful bilateral stent deployment in an appropriate position with the ability of contrast to readily flow through the stent and into the duodenum was used to define technical success [ 17 ]. Functional success is defined as at least a 30% reduction in total bilirubin within 2 weeks postoperatively, or 50% within 4 weeks [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Asia-Pacific Working Group recommended that biliary stent should drain more than 50% of the entire liver [ 7 ]. Therefore, bilateral stenting is preferred among a majority of researchers [ 11 17 ]. There are two commonly used bilateral stenting techniques, which include side-by-side (SBS) and stent-in-stent (SIS) strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation